Status competition and rising powers in global governance: an introduction - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This introductory article delves into the assessment of status policies and status seeking strategies of rising powers and most particularly their status competition among themselves in multiple platforms of global governance. Different from the competition engaged by a rising power against an established power, status competition among the rising peers creates different consequences in terms of both their intergroup relations and their relations towards the higher-status traditional powers. Status competition may also be used as a strategy by rising powers having equal or similar level of status in international organizations to find new fields of cooperation and to develop new diplomatic networks. Internal dynamics of rising powers and their leaders' foreign policy choices also shape the way and the degree to which they engage in status competition in status clubs. Status competition among rising powers may also contribute to the reinforcing of their status recognition.
Keywords: Status; status-seeking; status competition; rising powers; global governance